Revalidation of the spider genus Citharoceps Chamberlin, 1924 (Araneae, Segestriidae) - André Marsola Giroti; Antonio Brescovit (ZooKeys, 2015)
Citharoceps Chamberlin was diagnosed by the presence of a very distinctive stridulatory apparatus composed of two patches of ridges on the sides of the cephalic region, and a stridulatory thorn on the prolateral region of the femur I. Currently, this genus is a junior synonym of Ariadna Audouin, with the assumption that the stridulatory apparatus could constitute an exclusive feature of its unique known species, Citharoceps fidicina Chamberlin, currently senior synonym of Citharoceps californica Chamberlin & Ivie. In the present study, Citharoceps is revalidated and redescribed based on the occurrence of the stridulatory apparatus in C. fidicina and Segestria cruzana Chamberlin & Ivie, and also on the presence of distinguishable characters, such as the length of the labium-sternum junction, ventral median spine on male metatarsi I, and strong sclerotized interpulmonary fold in females, forming a conspicuous median flap. Segestria cruzana is transfered to Citharoceps, with C. californica removed from the synonym of C. fidicina, and proposed as a junior synonym of C. cruzana, due to the similarity between the additional material examined and the original description. Males of C. fidicina and C. cruzana are described for the first time.